2019
DOI: 10.1097/md.0000000000018062
|View full text |Cite
|
Sign up to set email alerts
|

Scalp acupuncture for children with cerebral palsy

Abstract: Background: Cerebral palsy (CP) describes a group of permanent disorders of movement and posture causing activity limitations, leading the most common movement disorder to children. Scalp acupuncture (SA) is one of several specialized acupuncture techniques, and it has been used widely in China to alleviate several CP symptoms, despite the deficiency of high-quality evidence related to this practice. Therefore, we plan to conduct a protocol of systematic review aimed at systematically reviewing all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Scalp acupuncture is a modern acupuncture technique that combines the traditional needling method with modern medical knowledge ( 21 ). It has been widely used to treat cerebral diseases in traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Scalp acupuncture is a modern acupuncture technique that combines the traditional needling method with modern medical knowledge ( 21 ). It has been widely used to treat cerebral diseases in traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…(30) The efficacy of SA in the treatment of post-stroke dysfunction has been confirmed recently in clinical studies and reports. (31,32) However, several studies reported that the curative effect of SA is not reliable. (33,34) The efficacy of acupuncture depends on the duration of hand-manipulation of needle and intensity of stimulation.…”
Section: Discussionmentioning
confidence: 99%